ANALISIS PREDIKSI KEBANGKRUTAN DENGAN METODE ALTMAN Z-SCORE PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Debby Eka Fitri Izmi; Uhud Darmawan Natsir; Nurman; Amiruddin Tawe; Anwar (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
This study aims to determine the potential for bankruptcy in food and beverage companies listed on the Indonesia Stock Exchange using the Altman Z-Score method. This type of research is a quantitative approach. The population in this study are all food and beverage companies listed on the Indonesia Stock Exchange. The samples in this study were 4 food and beverage companies which were included in the criteria set by the researcher. Data collection techniques are carried out with documentation. Data analysis technique using Altman Z-Score. The results of this study show that in 2017 there were 1 company in the "Safe Zone" category, namely AISA, there were 2 companies in the "Grey Zone" category, namely ALTO and BTEK, and there was 1 company in the "Distress Zone" category, namely AISA. 2018 which is in the "Safe Zone" category, namely none, there are 2 companies in the "Grey Zone" category, namely ALTO, BTEK and PSDN, and there is 1 company in the "Distress Zone" category, namely AISA. In 2019 there were companies in the "Safe Zone" category, namely none, there were 2 companies in the "Grey Zone" category, namely ALTO and PSDN, and there were 2 companies in the "Distress Zone" category, namely BTEK and AISA. In 2020 there are no companies in the "Safe Zone" category, there is 1 company in the "Grey Zone" category, namely PSDN, and there are 2 companies in the "Distress Zone" category, namely ALTO, BTEK and AISA. In 2021 there are no companies in the "Safe Zone" category, there is 1 company in the "Grey Zone" category, namely none, and there are 2 companies in the "Distress Zone" category, namely ALTO, BTEK, PSDN and AISA.